Anthropometric Phenotype of Patients with PMM2-CDG - Patryk Lipiński; Agnieszka Różdżyńska-Świątkowska; Anna Bogdańska; Anna Tylki-Szymańska (MDPI AG, 2021)
Background: Growth failure is commonly reported in children with PMM2-CDG. The aim of the study was to delineate the longitudinal anthropometric phenotype of patients with PMM2-CDG and attempt to find some correlations between the genotype and anthropometric phenotype. Materials and methods: Retrospective chart review of PMM2-CDG patients' medical records was performed regarding the anthropometric measurements (head circumference, body length/height, body weight, body mass index) and PMM2 variants. Results: A negative tendency of growth evolution was observed. Patients found to be heterozygous for R141H grew slower than other patients. Body weight was correlated with body height. A negative tendency of the growth rate of head circumference was observed. Patients found to be heterozygous for R141H experienced slower growth than other patients. Conclusions: Long-term observational studies are essential to characterize the anthropometric phenotype. The body growth failure, as well as head circumference growth failure, were more severe in patients found to be heterozygous for R141H.